Photoconductive semiconductor switch-based triggering with 1 ns jitter for trigatron - Langning Wang; Yongsheng Jia; Jinliang Liu (Matter and Radiation at Extremes, 2018)
AbstractSynchronization for multiple-pulse at nanosecond range shows a great value on the power multiplication and synchronous electric fields applications. Nanosecond or sub-ns jitter synchronization is essential for the improved working efficiency of the large amounts of pulse modules and accurate requirements for the power coherent combining applications. This paper presents a trigger generator based on a laser diode-triggered GaAs photoconductive semiconductor switch (PCSS) with low jitter and compact size characteristics. It avoids the high currents that are harmful to high-gain mode PCSSs. In the trigger circuit, a 200 pF capacitor is charged by a microsecond-scale 18 kV pulse and then discharged via the high-gain mode GaAs PCSS to trigger the high-power trigatron switch. When triggered by the ∼10 ns pulse generated by the PCSS, the DC-charged trigatron can operate in the 20–35 kV range with 10 ns rise time and 1 ns delay-time jitter.